Microbiologically Induced Corrosion of MIG Welded SPCC Low Carbon Steel by Shewanella oneidensis MR-1 Under Different Growth Condition - Lee Kai Yang (2022)
ron-reducing bacteria may deteriorate corrosion process when environment is supplemented with favoured terminal electron acceptors. This study aimed to examine the result of Shewanella oneidensis MR-1 under anaerobic and iron reducing condition on welded SPCC low carbon steel, since there has been insufficient study on microbiologically induced corrosion (MIC), typically on welded metal. In this study, the polished metal inert gas (MIG) welded metal were immersed in minimal MI medium for 7 days and 14 days of corrosion incubation, to examine the corrosion rate by S. oneidensis MR-1 on low carbon steel coupon and Fe (I concentration after 7 and 14 days of corrosion incubation in minimal MI medium. Surface morphology of the metal after corrosion incubation and mineral identification of the corrosion by-products were also conducted and investigated. An SPCC low carbon steel with a ER70S-6 filler wire welded with MIG welding technique, followed by cutting, and fit inside an epoxy resin. The metals were contained in universal bottle and then immersed in M1 medium, supplemented with and without electron acceptor (ferric citrate). The resulting corrosion rate and ferrous concentration of sample with S. oneidensis MR-1 with ferric citrate of 7 days is higher than of 14 days. In the case of without electron acceptor, there is no significant difference between 7 days and 14 days. This infers the active microbial activity on the first 7 days when cells were in exponential and stationary phase, however, enter death phase afterward. Formation of crystalline was observed after 7 days of corrosion incubation S. oneidensis MR-1 with ferric citrate. The biogenic corrosion by-products were then identified to be vivianite, hematite, magnetite, and siderite. This research paved a way for understanding S. oneidensis MR-1 in corrosion study with welded metal.